2013
DOI: 10.1002/adv.21394
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Current Electrical Properties of Thin Films of Plasma Polymerized 1, 1, 3, 3‐Tetramethoxypropane

Abstract: Plasma-polymerized 1, 1, 3, 3-tetramethoxy-propane (PPTMP) thin films are prepared by using a capacitively coupled glow discharge reactor. The dielectric constant and the alternating current (AC) electrical conductivity of the PPTMP thin films are investigated in the frequency range from 30 to 10 4 Hz, and in the temperature range from 298 to 423 K. The AC electrical conduction mechanism in the PPTMP thin films is observed to be dominated by hopping of carriers between localized states. The trend of dielectric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
2
11
0
1
Order By: Relevance
“…It is a clear colorless, inflammable liquid with slight pungent smell. Its chemical structure has been reported earlier [15].…”
Section: Methodsmentioning
confidence: 88%
See 3 more Smart Citations
“…It is a clear colorless, inflammable liquid with slight pungent smell. Its chemical structure has been reported earlier [15].…”
Section: Methodsmentioning
confidence: 88%
“…It is also observed that the σ ac increases as frequency increases in all samples with a higher slope in the mid frequency region. The dependence of σ ac on frequency can be described by the equation σactrue(ωtrue)=Aωn , where ω is the angular frequency, “ A ” is a constant independent of frequency, “ n ” is the index which is used to understand the type of conduction mechanism in noncrystalline materials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Where C is the capacitance of the sample, d is the thickness of the sample, ε 0 is the permittivity [3,29,30] When the frequency dependent dielectric constant for the thin film with thickness of 20 nm was investigated, it was observed that there were two relaxation mechanisms. One of these mechanisms was observed at frequencies lower than 100 Hz and the other mechanism was observed at frequencies higher than 100 Hz.…”
Section: Frequency and Temperature Dependence Of Dielectric Constant mentioning
confidence: 99%